(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the prevalence ofurinary tract infection innephrotic syndrome. Design: A descriptive study. Place and Duration of study: Department of Pediatric Medicine, Combined Military Hospital, Lahore, Pakistan. January 2003 to December 2009. Patients and Methods: During the study,all children with nephrotic syndrome, irrespective of the stage of their disease, were evaluated for the presence of UTI with a 12 month follow up period.The ages ranged between 1-14 years. Results: Out of the included 70 cases, between 1-14 years of age, 47 (67.1%) were boys and 23 (32.8%) girls in a ratio of 2.04:1.Twenty onepatients were newly diagnosed and the remaining 49children were known cases of nephrotic syndrome. Pyuria was seen in 22 (31.4%) cases, Covert bacteriuria in 32 (45.7%) and culture positive UTI in 18 (25.7%). Of the 18 culture positive cases, 13(72.2%) cases had primarily presented with a relapse, being treated with various immunosuppressive agents. Escherichia coliwas the commonest pathogen grown in 38.8% of the culture positive cases. Conclusion: UTI may be a significant co-existing infection in children suffering from NS. It is usually difficult to diagnose but needs early recognition and treatment.